Legal Force of Deeds of Sale and Purchase of Land And Buildings That Are Not Signed by the Seller - Deviyanti, Deviyanti; Wulandari, Andi Sri Rezky (Asosiasi Ide Bahasa Kepri, 2024)
This research uses a juridical approach, normative is a research method that focuses on the analysis of legal norms, statutory regulations and court decisions that are relevant to answering the legal problems faced. In this context, normative research will be used to analyze court decisions that are relevant to the topic under study. The results of this research show that the legal force of the Deed of sale and purchase of land and buildings which is not signed by the seller is that the Deed of Sale and Purchase of land and buildings must be signed by both parties, the seller and the buyer, to have legal force. In accordance with Article 37 Paragraphs (1) and (2) Government Regulation no. 24 of 1997, without the seller's signature, the deed cannot be used as a basis for registering changes to land rights at the land office. Sale and purchase transactions that do not meet these formal requirements can result in the sale and purchase deed being invalid, even though the transaction can remain valid on the basis of good intentions and payments that have been made. by the seller of Makassar District Court decision No.5/Pdt.G/2023/PN/Makassar is In case Number 5/Pdt.G/2023/PN/Makassar, the judge showed thoroughness in evaluating the evidence and considering all relevant legal elements. The judge ensures justice for the Plaintiff and determines the procedures that must be followed to correct the situation that is detrimental to the Plaintiff, reflecting the appropriate and comprehensive application of the law in this case.